TINJAUAN KOMPREHENSIF TEORI KEPRIBADIAN PSIKOANALISIS KLASIK, NEO-FREUDIAN, PARADIGMA GANGGUAN MENTAL DAN MEKANISME PERTAHANAN DIRI - Priskila Sinurat; Anggraini Natunggele; Angelita Ivana Martono; Veronika Juliet Kamasi; Melkian Naharia (JIPDAS (Jurnal Ilmiah Pendidikan Dasar), 2025)
This article is a systematic review that aims to analyze the development of personality theory from a psychodynamic perspective, from classical psychoanalysis to the Neo-Freudian approach. The review process was conducted by examining literature discussing Freud's basic concepts, the development of thought by Adler, Jung, Horney, Sullivan, and Fromm, and their relevance in explaining psychological dynamics and mental disorders. The results of the review indicate that psychodynamic theory has undergone significant expansion, from an emphasis on intrapsychic conflict and biological drives to a more holistic understanding involving social, interpersonal, and existential factors. This review also highlights the relationship between personality structure and defense mechanisms, as well as the fundamental differences between neurotic and psychotic disorders within a psychodynamic framework. Overall, this systematic review confirms that the psychodynamic approach continues to make important contributions to understanding human behavior, personality dynamics, and the formation of psychological symptoms, and is relevant for use as a conceptual foundation in clinical and academic studies.